Spoken Interaction and Grammatical Growth In Adult L2 Acquisition: A Case Of Interlanguage Evolution - Nurbiati; Thamrin, Sri Wahyuni (Jurnal Pendidikan Dasar Islam, 2025)
This research explores the development of interlanguage and sentence formation in an adult learner of a second language (L2) through naturally occurring spoken interactions. Grounded in (Selinker, 1972) theory of interlanguage and (Krashen, 1981) Input Hypothesis, the study investigates the learner’s progression from dependence on first language (L1) structures toward an emerging syntactic awareness in English. Data were obtained from two recorded interview sessions and analyzed qualitatively to examine patterns in vocabulary use, sentence construction, and communicative strategies. The findings show a gradual transition from predominantly lexical expressions with frequent code-mixing to efforts at forming more grammatically structured utterances. Although the learner still demonstrated limited grammatical accuracy and produced shorter sentences under more demanding input conditions, signs of improvement were evident in the correct use of verb forms and reduced reliance on L1. These outcomes align with recent research by (Ellis & Shintani, 2014; Ortega, 2013) and (Lightbown & Spada, 2020), which highlight the dynamic and non-linear nature of adult L2 acquisition. The study underscores the critical role of meaningful input, interactive dialogue, and cognitive engagement in fostering communicative competence.